Pecuniary and Non-Pecuniary Motivations for Tax Compliance: Evidence from Pakistan - Joel Slemrod; Obeid Ur Rehman; Mazhar Waseem (Center for Economic Studies and ifo Institute (CESifo), 2019)
We examine two Pakistani programs to explore the role of deterrence as well as social and psychological factors in the tax compliance behavior of agents. In the first of these programs, the government began revealing income tax paid by every taxpayer in the country. The second program publicly recognizes and rewards the top 100 tax paying corporations, partnerships, self-employed individuals, and wage-earners. We find that both public disclosure and social recognition of top taxpayers caused a substantial increase in tax payments. We explore the drivers of this behavior, including the shift of social norms toward compliance.
Keywords: H24; H25; H26; 330; tax evasion; income tax; social norms